Application of the Newton–Raphson Method to Compare Effective Interest Rates for Motorcycle Installments - Tampubolon, Monica Noviyanti; Candra Ditasona; Siregar, Jeny; Simbolon, Rido (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
Purchasing a motorcycle on credit is a popular option for many people in Indonesia. However, information about financing provided to consumers usually only includes the down payment amount, monthly installments, and credit term, without providing details about the effective interest rate. This makes it difficult for consumers to compare different credit schemes fairly. This study aims to use the Newton-Raphson method to determine and compare the effective interest rates of Honda Beat CBS and Yamaha Mio M3 CW motorcycle installments. The data used in this study was taken from official financing brochures for a 23-month period. The effective interest rate was determined by solving nonlinear equations for fixed installment loans using the Newton-Raphson method. The results of the study show that although the monthly installments for both motorcycles are quite similar, there are differences in effective interest rates that cannot be seen directly from the installment amounts. The Newton-Raphson method has been proven to provide accurate and structured solutions that are easy to use. Therefore, this method can be used as an objective tool for analyzing and comparing motorcycle credit financing.